Discovery of a Fanaroff–Riley type 0 radio galaxy emitting at γ-ray energies. Issue 1 (19th January 2016) - Grandi, Paola; Capetti, Alessandro; Baldi, Ranieri D.
Abstract: We present supporting evidence for the first association of a Fermi source, 3FGLJ1330.0−3818, Acero et al. (2015) with the Fanaroff–Riley type 0 (FR 0) radio galaxy Tol1326−379. FR 0s represent the majority of the local population of radio-loud active galactic nuclei but their nature is still unclear. They share the same nuclear and host properties as FR Is, but they show a large deficit of extended radio emission. Here we show that FR 0s can emit photons at very high energies. Tol1326−379 has a GeV luminosity of L >1 GeV ∼ 2 × 10 42 erg s −1, typical of FR Is, but with a steeper γ-ray spectrum (Γ = 2.78 ± 0.14). This could be related to the intrinsic jet properties but also to a different viewing angle.